Big Data and Current Cloud Computing Issues and Challenges (International Journal of Engineering and Computer Science, 2017)
Big data applications are a great benefit to organizations, business, companies and many large scale and small scale industries .We also discuss various possible solutions for the issues in cloud computing security and Hadoop. Cloud computing security is developing at a rapid pace which includes computer security, network security, information security, and data privacy. Cloud computing plays a very vital role in protecting data, applications and the related infrastructure with the help of policies, technologies, controls, and big data tools. Big data is a data analysis methodology enabled by recent advances in technologies and architecture. Cloud computing is a set of it services that are provided to a customer over a network on a leased basis and with the ability to scale up or down their service requirements. It advantages includes scalability, resilience, flexibility, efficiency and outsourcing non-core activities.